Silver Nano/microparticles: Modification and Applications - Rho, Won Yeop (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Nano/micro-size particles are widely applied in various fields. Among the various particles, silver particles are considered among the most prominent nanomaterials in the biomedical and industrial sectors because of their favorable physical, chemical, and biological characteristics. Thus, numerous studies have been conducted to evaluate their properties and utilize them in various applications, such as diagnostics, anti-bacterial and anti-cancer therapeutics, and optoelectronics. The properties of silver particles are strongly influenced by their size, morphological shape, and surface characteristics, which can be modified by diverse synthetic methods, reducing agents, and stabilizers. This Special Issue provides a range of original contributions detailing the synthesis, modification, properties, and applications of silver materials. Nine outstanding papers describing examples of the most recent advances in silver nano/microparticles are included. Silver nano/micro-size particles have many potential advantages as next-generation materials in various areas, including nanomedicine. This Special Issue might be helpful to understand the value of silver particles in the biomedical and industrial fields